The Giver of Stars - Moyes, Jojo 1969- ([New York, NY] : Pamela Dorman Books/Viking, 2019)
"Alice Wright marries handsome American Bennett Van Cleve hoping to escape her stifling life in England. But small-town Kentucky quickly proves equally claustrophobic, especially living alongside her overbearing father-in-law. So when a call goes out for a team of women to deliver books as part of Eleanor Roosevelt's new traveling library, Alice signs on enthusiastically. The leader, and soon Alice's greatest ally, is Margery, a smart-talking, self-sufficient woman who's never asked a man's permission for anything. They will be joined by three other singular women who become known as the Horseback Librarians of Kentucky. What happens to them--and to the men they love--becomes a classic drama of loyalty, justice, humanity and passion. Though they face all kinds of dangers, they're committed to their job--bringing books to people who have never had any, sharing the gift of learning that will change their lives. Based on a true story rooted in America's past, The Giver of Stars is unparalleled in its scope. At times funny, at others heartbreaking, this is a richly rewarding novel of women's friendship, of true love, and of what happens when we reach beyond our grasp for the great beyond"--
Keywords: Packhorse librarians -- Fiction; Librarians -- Fiction; Female friendship -- Fiction; Kentucky -- Fiction; Historical fiction; Romance fiction